The Rhesus Macaque as a Translational Model for Neurodegeneration and Alzheimer’s Disease - Stonebarger, Gail A.; Bimonte-Nelson, Heather A.; Urbanski, Henryk F. (Frontiers in Aging Neuroscience, 2021)
A major obstacle to progress in understanding the etiology of normative and pathological human brain aging is the availability of suitable animal models for experimentation. The present article will highlight our current knowledge regarding human brain aging and neurodegeneration, specifically in the context of Alzheimer’s disease (AD). Additionally, it will examine the use of the rhesus macaque monkey as a pragmatic translational animal model in which to study underlying causal mechanisms. Specifically, the discussion will focus on behavioral and protein-level brain changes that occur within the central nervous system (CNS) of aged monkeys, and compare them to the changes observed in humans during clinically normative aging and in AD.